Operations and Supply Chain Optimization – The New Era Model - Rajesh Chennattu Sasidharan Nair (International Journal of Supply Chain Management, 2022)
Purpose:This article is an investigative study of optimization of supply chain and hence operations in the new era of digitization and identifies scope for future studies and further development of ways to achieve operational excellence. Design/ Methodology/ Approach:This research uses literature review and case studies to highlight the evolution of supply chain in the present era. The focus is on operational modifications the took place following the disruptions caused by such factors as technological innovations and global pandemic. This study employs the method of case study to support and substantiate the knowledge.Findings:The COVID-19 pandemic has demonstrated to the world that supply chain is the true lifeline of any business operation. The manufacturers had been hitherto concentrating on long-term planning to decide their future course of action and the organizational strategy. The COVID-19 pandemic exposed the futility and vulnerability of long-term planning and the need for short-term ad-hoc decision-making ability.Recommendation Conclusion:It is necessary to optimize supply chain and operations to build in resilience and flexibility to ensure faster response to unforeseen disruptions. Short term responsiveness is gaining popularity and building resilience must overtake forecasting to ensure shocks such as Covid do not throw businesses completely out of gear.